Pengaruh Fear of Missing Out (FoMO), Kontrol Diri dan Pembiasaan Ibadah Harian terhadap Pengamalan Nilai-Nilai Pendidikan Agama Islam (PAI) Siswa SMP Al Muslim - Nufus Farichah (Lembaga Pengembangan Kinerja Dosen, 2026)
The quick advancement of digital technology has drastically changed the social and religious life of Indonesian teenagers. The purpose of this study is to investigate how pupils at Al Muslim Junior High School's daily worship practices, self-control, and fear of missing out (FoMO) affect the principles of Islamic Religious Education (PAI). The study used a quantitative methodology with a causal and correlational design. All students in grades VII, VIII, and IX made up the study population for the 2025–2026 school year. Using the Slovin formula, a proportionate stratified sample of 171 students with a 5% margin of error was chosen. A five-point Likert scale questionnaire was used to gather data. The Pearson Product-Moment correlation (r > 0.30) was used to evaluate validity, while Cronbach's Alpha (α > 0.70) was used to test reliability. Multiple linear regression using SPSS version 26 was used for quantitative analysis, beginning with traditional assumption tests for heteroscedasticity (Glejser), multicollinearity (VIF), and normality (Kolmogorov-Smirnov). According to the analysis results, self-control had a substantial, favorable impact on the practice of PAI values, but FoMO had no significant influence (β = -0.034, p = 0.530).